Quantum non-locality and relativity metaphysical intimations of modern physics - Maudlin, Tim (Chichester, West Sussex, [England] Wiley-Blackwell, 2011)
"Quantum Non-Locality and Relativity is recognized as the premier philosophical study of Bell's Theorem and its implication for the relativistic account of space and time. Previous editions have been praised for the remarkable clarity of Maudlin's descriptions of both Bell's theorem and his examination of the potential conflict between the theorem and relativity. The third edition of this text has been carefully updated to reflect significant developments, including a new chapter covering important recent work in the foundations of physics. Foremost among these is Roderich Tumiulka's explicit, relativistic theory that can reproduce the quantum mechanical violation of Bell's inequality. The "Free Will Theorem" of John Conway and Simon Kochen is also discussed, as is the status of locality in the Many Worlds interpretation of quantum theory. The book has also been updated to reflect recent results in information theory. The book introduces philosophers to the relevant physics and demonstrates how philosophical analysis can help to resolve some of the problems, and requires no technical background in Physics. All of the physics is presented from first principles, and as much as possible is presented pictorially"--Provided by publisher.
1. Bell's Theorem: The Price of Locality -- 2. Relativity and Space-time Structure -- 3. Finger Exercise: Superluminal Matter Transport -- 4. Controlling the Connection: Signals -- Appendix B: Bohmian Mechanics -- 5. Causation -- 6. Secret Messages -- 7. Points of View -- 8. Life in Elastic Space-time -- 9. Morals -- 10. New Discoveries and Deeper Insights: The View from 2010 -- An Overview of Quantum Mechanics.
"A John Wiley & Sons, Ltd., publication."
Includes bibliographical references and index.
Keywords: Physics -- Philosophy; Quantum theory; Relativity (Physics)